Respuesta :

Answer:  p = 4, r = 4

Step-by-step explanation:

The equation of a circle is:   (x - h)² + (y - k)² = r²     where

  • (h, k) is the center of the circle
  • r is the radius of the circle

Complete the square:

x² - 10x +  _____   +     y² + py + _____     = -13 + ___ + ___

x² - 10x  + (-10/2)² +     y² + py + (p/2)²     = -13 + (-10/2)² + (p/2)²        

                  (x - 5)²  +     (y + p/2)²                = -13 + 25 + (p/2)²

                        ↓                   ↓                          |__________|      

                      h = 5              k = -p/2                            r²

Given: (h, k) = (5, -2)

                                          -2 = -p/2

                                          -4 = -p

                                            4 = p

   r² =  -13 + 25 + (p/2)²

       = -13 + 25 + (4/2)²

       = -13 + 25 + 4

       = 16

[tex]\sqrt{r^2}=\sqrt{16}[/tex]

  r  =  4